2009
DOI: 10.1088/0031-9155/54/13/014
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo modeling of cascade gamma rays in86Y PET imaging: preliminary results

Abstract: 86Y is a PET agent that could be used as an ideal surrogate to allow personalized dosimetry in 90Y radionuclide therapy. However, 86Y also emits cascade gamma rays. We have developed a Monte Carlo program based on SimSET to model cascade gamma rays in PET imaging. The new simulation was validated with the GATE simulation package. Agreements within 15% were found in spatial resolution, apparent scatter fraction (ratio of coincidences outside peak regions in line source sinograms), singles and coincidences stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…Finally, a possible but time-consuming solution is a full Monte Carlo simulation of the emission and interaction of all radiation in the prompt gamma radioisotopes. Fast-simulation packages for PET like SimSET have been used [ 46 ]. GATE Monte Carlo simulation was successful for a complete simulation of non-pure radioisotopes, and it was used as a support for estimating suitable functions modeling the tails of the sinograms.…”
Section: Reviewmentioning
confidence: 99%
“…Finally, a possible but time-consuming solution is a full Monte Carlo simulation of the emission and interaction of all radiation in the prompt gamma radioisotopes. Fast-simulation packages for PET like SimSET have been used [ 46 ]. GATE Monte Carlo simulation was successful for a complete simulation of non-pure radioisotopes, and it was used as a support for estimating suitable functions modeling the tails of the sinograms.…”
Section: Reviewmentioning
confidence: 99%
“…Bading et al [ 36 ] examined the degradation of image resolution, when 124 I was used comparatively with 18 F in a microPET R4 small animal scanner (Concorde/Siemens, Knoxville, TN, USA). In the scanner’s centre the FWHM was 2.3 mm for 124 I and 1.9 mm for 18 F. Using a Discovery STE PET/CT scanner Zhu and El Fakhri [ 37 ] studied the spatial resolution of 18 F and 86 Y with a line source placed centrally in air and reported values of 5.56 and 6.06 mm. Gregory et al reported a resolution degradation of 0.7 mm for 124 I compared to 18 F for the Gemini Dual GS PET/CT scanner [ 28 ].…”
Section: Resolution and Recoverymentioning
confidence: 99%
“…The output sinograms covered a 15.7cm axial field of view (FOV). The number of transaxial and angular bins were 128 and 140, respectively and 192 was the number of axial slices (1 cm slice size) [22].…”
Section: Impactmentioning
confidence: 99%